2007
DOI: 10.1194/jlr.m600501-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

OKL38 is an oxidative stress response gene stimulated by oxidized phospholipids

Abstract: Oxidized 1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphorylcholine (OxPAPC) is present in oxidative modified LDL and accumulates in lesions of many chronic inflammatory diseases, such as atherosclerosis. In a microarray study, OxPAPC has been demonstrated to modulate the expression of .700 genes in human aortic endothelial cells. We found that the levels of mRNA for OKL38 [also named Bone marrow Derived Growth Factor (BDGI)], a tumor growth inhibitor, were strongly increased by OxPAPC. Here, we report that OKL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 36 publications
5
54
0
1
Order By: Relevance
“…The similarity of structure in these two molecules suggested that they might have similar interactions with cell proteins. Previous studies have shown similar effects of 15dPGJ 2 to OxPAPC in several pathways ( 7,9,12,14,15,(22)(23)(24)(25)(26)(27). We now demonstrate that OxPNB and 15dPGJ 2 bind to the same cysteines in H-Ras (C181 and C184) and that 15dPGJ 2 can inhibit the binding of OxPNB to H-Ras.…”
Section: Discussionsupporting
confidence: 53%
“…The similarity of structure in these two molecules suggested that they might have similar interactions with cell proteins. Previous studies have shown similar effects of 15dPGJ 2 to OxPAPC in several pathways ( 7,9,12,14,15,(22)(23)(24)(25)(26)(27). We now demonstrate that OxPNB and 15dPGJ 2 bind to the same cysteines in H-Ras (C181 and C184) and that 15dPGJ 2 can inhibit the binding of OxPNB to H-Ras.…”
Section: Discussionsupporting
confidence: 53%
“…A newly recognized anti-oxidant gene, OKL 38, is also induced by Ox-PAPC. Regulation of HO-1 transcription has been examined by two groups, who have identified two different pathways involved in this regulation: Kronke et al identified a MAP kinase/CREB pathway of activation in HUVEC 48 , while Li et al identified a pathway involving the activation of Nrf2 16 in HAEC. Induction of these antioxidant enzymes is likely to protect the cell from cell death, which is negligible in response to Ox-PAPC.…”
Section: Regulation Of Oxidative Stressmentioning
confidence: 99%
“…The array and cell biology studies have highlighted several transcription factors important in Ox-PAPC action, such as STAT3, SREBP, Nrf2, erg-1, NFAT and transcription factors of the UPR system. 15,16 In this review, we will address the roles of these transcription factors as well as other signaling molecules in Ox-PAPC signaling. Since Ox-PAPC contains a mixture of oxidized phospholipids, studies with the individual phospholipids have also been reported and will be discussed in this review.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with an increased production of ROS, oxPAPC may stimulate the transcription of oxidative stress response genes, such as OKL38, a key regulator of important inflammatory and anti-inflammatory molecules [201]. Expression of OKL38 has been observed to be mediated by Nrf2 [202].…”
Section: Up-regulation Of Chemokines Inflammatory Cytokines and Growmentioning
confidence: 99%